Ri’asatu Ny. Wiwik Prasetiyo Ningsih wa Dauruha fi Ta’lim al-Lughah al-‘Arabiyyah - Hamdy, Mohammad Zainal (Al-Abshar: Journal of Islamic Education Management, 2024)
Teachers are an important aspect in learning Arabic which today faces a lot of competition from other languages ​​as time goes by. Arabic needs a figure who can be an example and catalyst in making learning Arabic interesting. This research uses qualitative Grounded Theory type where the researcher personally experiences things related to the theme over a relatively long period of time. The results of this research are that the role of Mrs. Wiwik Prasetiyo Ningsih is very big in Arabic, especially in the field of literacy, with his democratic leadership and behaviorist approach, he has produced many works in Arabic language learning which can help students as well as teachers enjoy studying Arabic